BIMBINGAN KONSELING PRA-NIKAH BAGI REMAJA DI KOTO TANGAH KOTA PADANG - Jasman Jasman; Rosdialena Rosdialena; Thaheransyah Thaheransyah; Muhammad Hafiz (LPPM Universitas Muhammadiyah Sumatera Barat, 2022)
ABSTRACTPremarital counseling is a knowledge and skills-based training that provides information about marriage that can be useful for maintaining and improving the relationship of a couple who is about to marry. One of the important activities raised in this service is the need for pre-marital counseling guidance for teenagers in the Pasie Jambak Village, Koto Tangah District, Padang City when they are going to hold a wedding. In addition, this service aims to increase the knowledge, insight and understanding of teenagers about problems that often occur in marriage and the right solutions to solve problems that arise in the family after marriage. The service method is carried out by holding pre-marital counseling guidance activities for adolescents. The results of the service by mapping the minimum age of teenagers to get married, preparing teenagers for marriage, and determining the ideal husband and wife. For this reason, the research team provides training to equip and provide knowledge to teenagers about preparation for marriage, so that they have sufficient insight and emotional strengthening to start married life. In addition, continuous education is also needed because in the family education is a process of cultural transformation that can influence family members in thinking and acting in everyday life. Efforts to raise awareness of the age of couples who are getting married need to be socialized so that there will be no problems in marriage in the future. If there are problems in marriage, mediation is needed so that disputes between husband and wife can be reconciled. The conclusion of this service is that teenagers already know and understand preparations both physically and psychologically if there has been a marriage, therefore it is important to appoint pre-marital counseling guidance for adolescents before marriage.Keywords : counseling, pre wedding, teenager